Bad year ahead? - Abd Razak, Dzulkifli (2006)
described the coming year in the Chinese lunar calendar. Generally, it is said the Fire Dog Year is not a good year, with some predicting the year as a year of diseases. One feng shui master had categorically said that "the bird flu epidemic will worsen". Eleventh in the lunar calendar cycle, Dog years follow Rooster years. This time, given the prevailing bird flu threat, it looks like the Rooster, which is considered a bird (family: Phasianidae) will continue to make its presence felt. Already, experts are worried that the deadly H5N1 virus could pose a big threat as people slaughter chickens for the New Year celebrations.